PENGEMBANGAN APLIKASI PENCARIAN HADIST RIYADHUS SHALIHIN IMAM NAWAWI JILID II PILIHAN BERBASIS ANDROID - Dwi Sakethi; Rangga Firdaus; Harjo Apkuanbo (Jurnal Komputasi, 2014)
Some muslims had so many reason not to learning Hadist, The statement and activity of Phophet Muhammad that used to guide the life of muslim. The objective of this research was to develop Android based application contains Hadist in Riyadhus Shalihin book vol. 2 by Imam Nawawi. In English Riyadhus Shalihin also known as Field of Meadow. Android Developer Tools by Eclipse and Droid draw for button placement is used by developer to create the application. The application used Java and XML as a programming language. The application is made to be used on Mobile phones based on Android operating system. Some features of the application is ability to choose theme based 100 themes in Riyadhus Shalihin book vol. 2, basic knowledge about Hadist, who is Imam Nawawi that contain Imam Nawawi biography, About Developer and an exit menu to exit the application.Keywords: Riyadhus Shalihin vol. 2,Field of Meadow vol. 2, Imam Nawawi, Android Application,Android Mobile, Android Developer Tool, Droid Draw, Java, XML.